Induction of WNT16 via Peptide-mRNA Nanoparticle-Based Delivery Maintains Cartilage Homeostasis - Huimin Yan; Ying Hu; Antonina Akk; Muhammad Farooq Rai; Hua Pan; Samuel A. Wickline; Christine T.N. Pham (MDPI AG, 2020)
Osteoarthritis (OA) is a progressive joint disease that causes significant disability and pain and for which there are limited treatment options. We posit that delivery of anabolic factors that protect and maintain cartilage homeostasis will halt or retard OA progression. We employ a peptide-based nanoplatform to deliver Wingless and the name Int-1 (WNT) 16 messenger RNA (mRNA) to human cartilage explants. The peptide forms a self-assembled nanocomplex of approximately 65 nm in size when incubated with WNT16 mRNA. The complex is further stabilized with hyaluronic acid (HA) for enhanced cellular uptake. Delivery of peptide-WNT16 mRNA nanocomplex to human cartilage explants antagonizes canonical β-catenin/WNT3a signaling, leading to increased lubricin production and decreased chondrocyte apoptosis. This is a proof-of-concept study showing that mRNA can be efficiently delivered to articular cartilage, an avascular tissue that is poorly accessible even when drugs are intra-articularly (IA) administered. The ability to accommodate a wide range of oligonucleotides suggests that this platform may find use in a broad range of clinical applications.